Section 37C of the Pension Funds Act, 24 of 1956 : a social security measure to escape destitution - Matotoka, Motlhatlego Dennis (University of Limpopo (Turfloop Campus), 2013)
The study will analyse section 37C of the Pension Funds Act, 24 of 1956. This section limits the deceased’s freedom of testate by placing the death benefits and the control of the board of trustees who are tasked to distribute such benefits equitably among the dependants and nominees of the deceased. Section 37C of the Act was enacted to protect dependency by ensuring that the dependants of the deceased are not left in destitute. In order to achieve this, three duties are placed on the board of trustees namely, to identify the dependants and nominees of the deceased member; to effect an equitable distribution of the benefit among the beneficiaries; and to determine an appropriate mode of payment. This section sees to all the interest of the dependants without discriminating consequently there are three classes of dependants that are created under section 37C namely; legal dependants, non-legal dependants, and future dependants.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2013
Keywords: Pension Funds Act; Social security; Pensions -- Law and legislation -- South Africa; Pension trusts -- Finance -- Law and legislation -- South Africa; Social security -- South Africa